2022
DOI: 10.1016/j.xfss.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The hypo-osmotic swelling test: Is it a sperm vitality or a viability assay?

Abstract: The first two editions of the World Health Organization laboratory manual described the determination of live spermatozoa by a dye exclusion method as a sperm ''viability'' test, whereas subsequent editions classified it as a ''vitality'' test, without providing an explanation for the reclassification. Additionally, the hypo-osmotic swelling (HOS) test, which assesses the functional integrity of the human sperm membrane, was placed in the same category as the dye exclusion test. Although the two terms might se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There are many fertility specialists who think that the HOS test and sperm vitality are synonymous, or at least test the same thing. In fact, this is not true [21]. As expected, there were no males with subnormal vitality tests who had normal HOS test scores [20].…”
Section: The Association Of Low Hos Test Scores and Other Subnormal S...mentioning
confidence: 82%
See 2 more Smart Citations
“…There are many fertility specialists who think that the HOS test and sperm vitality are synonymous, or at least test the same thing. In fact, this is not true [21]. As expected, there were no males with subnormal vitality tests who had normal HOS test scores [20].…”
Section: The Association Of Low Hos Test Scores and Other Subnormal S...mentioning
confidence: 82%
“…Although the two terms might seem synonymous the term "vitality" merely means "alive" whereas "viability" assesses qualities or physiological function of a living entity. After comparing the morphological, physiological and clinical findings obtained from dye exclusion testing vs. the HOS test, we concluded that the HOS test should be classified as a viability test, not merely as a vitality test" [21]. Whereas males with AOT would be likely to have both abnormal dye exclusion tests and low HOS test scores (a structural defect in the sperm membrane will lead to a functional defect as well), males with otherwise normal semen parameters are very unlikely to have an abnormal dye exclusion test, yet a low HOS test score is very possible.…”
Section: Other Possible Ways To Negate the Adverse Effect On Female F...mentioning
confidence: 98%
See 1 more Smart Citation